EFFECT OF ACCOUNTING INFORMATION SYSTEM EFFECTIVENESS, INFORMATION TECHNOLOGY UTILIZATION AND TASK FIT ON PERFORMANCE WITH WORK SATISFACTION AS MODERATING VARIABLES IN THE EDUCATION OFFICE OF NORTH SUMATERA PROVINCE - Hasibuan, Mahdanisa Anggita (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to obtain empirical evidence about the Effect of Accounting Information Systems Effectiveness, Information Technology Utilization, Task Fit on Employee Performance with Job Satisfaction as Moderation Variables. Sampling using a census. Where the total population is a sample of employees who use accounting information systems and information technology as many as 178 respondents. This research uses Eviews software. The results of this study indicate that Accounting Information Systems Effectiveness and Task Fit have no significant effect on Performance, while Information Technology Utilization has a significant effect on performance, and Job Satisfaction is able to moderate the effect between Accounting Information Systems Effectiveness and Information Technology Utilization on employee performance by strengthening the effect, whereas on Task Fit variable Job Satisfaction moderates by weakening its effect.